2020
DOI: 10.3389/fphar.2020.582719
|View full text |Cite
|
Sign up to set email alerts
|

Targets and Mechanism Used by Cinnamaldehyde, the Main Active Ingredient in Cinnamon, in the Treatment of Breast Cancer

Abstract: Background: Breast cancer has become one of the most common malignant tumors in women owing to its increasing incidence each year. Clinical studies have shown that Cinnamomum cassia (L.) J. Presl (cinnamon) has a positive influence on the prevention and treatment of breast cancer.Aim: We aimed to screen the potential targets of cinnamon in the treatment of breast cancer through network pharmacology and explore its potential therapeutic mechanism through cell experiments.Methods: We used the TCMSP, TCM Database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“… Nour et al (2018 ), Abdelmageed et al (2019 ), and Wang et al (2020 ) also found that CA not only reduces atherosclerosis induced by high-cholesterol diet in rabbits but also has therapeutic potential for diabetes mellitus. A number of studies have identified that CA inhibited the proliferation and metastasis of cancers ( Li et al, 2016 ; Wu et al, 2019 ; Liu et al, 2020 ). Liu et al (2020) reported that CA inhibited the proliferation and invasion of breast cancer, and the PI3K/AKT signaling pathway is its potential target through KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Nour et al (2018 ), Abdelmageed et al (2019 ), and Wang et al (2020 ) also found that CA not only reduces atherosclerosis induced by high-cholesterol diet in rabbits but also has therapeutic potential for diabetes mellitus. A number of studies have identified that CA inhibited the proliferation and metastasis of cancers ( Li et al, 2016 ; Wu et al, 2019 ; Liu et al, 2020 ). Liu et al (2020) reported that CA inhibited the proliferation and invasion of breast cancer, and the PI3K/AKT signaling pathway is its potential target through KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified that CA inhibited the proliferation and metastasis of cancers ( Li et al, 2016 ; Wu et al, 2019 ; Liu et al, 2020 ). Liu et al (2020) reported that CA inhibited the proliferation and invasion of breast cancer, and the PI3K/AKT signaling pathway is its potential target through KEGG analysis. Li et al (2016) found that CA reduced the expression level of MMPs, the key proteins that downregulated cell adhesion ability in colorectal cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main compound in the cinnamon oil is cinnamaldehyde 18 , 19 . Cinnamaldehyde or transcinnamaldehyde is known by its antimicrobial, antipyretic and anti-inflammatory potencies 18 , also it exert anticancer activities via controlling tumor cell growth, proliferation capabilities, inducing apoptosis and necrosis of tumor cells 19 , 20 . Another active ingredients of cinnamon oil are eugenol and cinnamic acid which are known by their antitumorgenesis role through inducing tumor cell apoptosis and exerting antioxidative properties 14 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%